USING STRONG ELECTRIC FIELDS IN THE GRAIN INDUSTRY - Usenko, S. (Енергетика і автоматика, 2016)
Presented developed ways of handling grain mass in a strong electric field in order to stimulate growth processes, decontamination and disposal of harmful microorganisms pests. The results of the developed methods of processing.